The Golden Age of Islamic Intellectuals and The Development of Science During The Abbasid Dynasty - Rusydi, Ibnu; Saepudin, Didin; Murodi, Murodi (Tafkir: Interdisciplinary Journal of Islamic Education, 2023)
This paper aims to examine the era of Islamic intellectual packaging during the reign of Caliph Harun al-Rashid during the Abbasid dynasty in Baghdad. History has recorded that during the reign of the Abbasid dynasty, Muslims were truly at the peak of their glory and led world civilization at that time. The reign of the Abbasid dynasty was a "golden age" in the history of Islamic civilization, especially during the reign of Caliph Harun al-Rashid and al-Ma'mun.  Harun al-Rashid is considered by historians to be the greatest and most brilliant caliph who brought the Abbasid dynasty to its golden age. He ruled for 23 years and made this dynasty achieve progress and glory in the fields of politics, economy, trade, science and Islamic civilization. This research concludes that the Abbasid Dynasty was the heyday of Islam in various fields, especially science and science. Islamic intellectual progress at that time was due to the caliph's love of science, the establishment of the Baitul Hikmah library, and the movement to translate various books and literature into and out of Arabic played a major role in shaping the Islamic intellectual world at that time.